Respecting the Voices of Individuals from Marginalised Communities in Research - Shevlin, Michael; Rose, Richard (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
International governments have committed to supporting the development of greater equity and inclusion in education. However-despite some progress-many individuals and communities continue to face discrimination, remaining on the margins of society. This collection of papers highlights the many challenges faced by persons perceived to be different from the majority population in their communities. This labelling of individuals has served to exclude many from engaging fully with the social and educational opportunities that the majority take for granted. The authors who have contributed to this Special Edition have challenged the stereotypical views of such individuals, ensuring that the voices of those who best understand the experience of living with discrimination can be heard.These papers demonstrate how listening to the voices of marginalised individuals can become an important first step towards a process of change. Such an action fundamentally challenges established procedures whereby opportunities to learn from the experiences of marginalised individuals have been neglected. We acknowledge that listening is only the starting point for a radical reengagement that enables marginalised individuals to fully participate in society. However, several of the authors who have contributed to this Special Edition have provided an indication of how the movement towards equity and inclusion may be advanced.